Karin Friedrich, The Other Prussia. Royal Prussia, Poland and Liberty, 2000 - Makiłła, Dariusz (Czasopismo Prawno-Historyczne, 2003)
Recenzja: Karin Friedrich, The Other Prussia. Royal Prussia, Poland and Liberty, 1569-1772, Cambridge University Press, 2000, ss. 280.